2007
DOI: 10.1063/1.2825416
|View full text |Cite
|
Sign up to set email alerts
|

Light scattering study of acoustic phonon modes and central peaks in Pb[(Mg1∕3Nb2∕3)0.45Ti0.55]O3 single crystals

Abstract: The dynamic polar nanoregions ͑PNRs͒ which form below the Burns temperature and determine the unique properties of relaxor ferroelectrics were predicted ͓Tinte et al., Phys. Rev. Lett. 97, 137601 ͑2006͔͒ to be pinned to the quenched chemically ordered regions ͑CORs͒ usually observed in lead-containing relaxors. In Pb͓͑Mg 1/3 Nb 2/3 ͒ 0.45 Ti 0.55 ͔O 3 crystal where CORs are known to be absent, we have found the phenomena typically related to the relaxation of dynamic PNRs, namely, the significant Brillouin qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 10 publications
6
47
1
Order By: Relevance
“…In relaxor ferroelectrics, CP that begins to appear well above T m is attributed to the relaxational dynamics of PNRs. 5,7 As shown in Fig. 7, the decrease in the width and increase in the integrated intensity of CP indicates critical slowing down of the relaxation time and increase in the correlations between the PNRs with decrease in temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In relaxor ferroelectrics, CP that begins to appear well above T m is attributed to the relaxational dynamics of PNRs. 5,7 As shown in Fig. 7, the decrease in the width and increase in the integrated intensity of CP indicates critical slowing down of the relaxation time and increase in the correlations between the PNRs with decrease in temperature.…”
Section: Resultsmentioning
confidence: 99%
“…2 Extensive studies on the dynamical aspects of PNRs have been carried out in prototype RFEs such as Pb(Mg 1/3 Nb 2/3 )O 3 (PMN) and other related systems through neutron and light scattering studies. [3][4][5][6][7][8][9] Brillouin scattering studies in these systems directly revealed the dynamical features of the PNRs such as the slowing down of their relaxation time and the coupling between the polarization fluctuations and acoustic phonon modes through the appearance of central peak (CP) and softening of the acoustic phonon mode. [6][7][8][9] This paper focuses on micro-Brillouin scattering studies on the dynamical aspects of PNRs in partially ordered Pb(Sc 1/2 Ta 1/2 )O 3 (PST) without any Pb vacancies.…”
Section: Introductionmentioning
confidence: 99%
“…In both heating and cooling processes, a significant softening of the LA mode and a clear anomaly corresponding to the cubic-tetragonal phase transition are observed at 481 K (T C-T ), which can be attributed to the interaction between the LA mode and the polarization flipping inside the dynamic PNRs. 16 The observed anomalous temperature dependence is similar to that of PMN-55PT with no COR, 15,28 while such a sharp elastic anomaly is uncharacteristic in typical RFEs such as PMN, PZN with CORs. In addition, LA shows a mild softening below T B $ 700 K, demonstrating that only normal anharmonic effects dominate in the lattice dynamics above T B .…”
Section: A Elastic Anomalymentioning
confidence: 61%
“…The temperature dependence of C LA , which is related to the acoustic damping of the LA mode, shows the sharp increase near T C-T , suggesting the increase of scattering of the LA mode by the growth of dynamic PNRs. 15,16 …”
Section: A Elastic Anomalymentioning
confidence: 99%
See 1 more Smart Citation